2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7318561
|View full text |Cite
|
Sign up to set email alerts
|

Detecting intention to grasp during reaching movements from EEG

Abstract: Abstract-Brain-computer interfaces (BCI) have been shown to be a promising tool in rehabilitation and assistive scenarios. Within these contexts, brain signals can be decoded and used as commands for a robotic device, allowing to translate user's intentions into motor actions in order to support the user's impaired neuro-muscular system. Recently, it has been suggested that slow cortical potentials (SCPs), negative deflections in the electroencephalographic (EEG) signals peaking around one second before the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…No significant differences in performance between recording systems could be found anymore. Unfortunately, a direct comparison to other reach-and-grasp studies such as ( Agashe et al, 2015 ; Randazzo et al, 2015 ; Iturrate et al, 2018 ) is difficult due significant differences in experimental setup and paradigm and hence cannot be made in a serious manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences in performance between recording systems could be found anymore. Unfortunately, a direct comparison to other reach-and-grasp studies such as ( Agashe et al, 2015 ; Randazzo et al, 2015 ; Iturrate et al, 2018 ) is difficult due significant differences in experimental setup and paradigm and hence cannot be made in a serious manner.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have shown that brain patterns of singular upper limb movements can be identified and decoded from EEGs’ low frequency time domain (LFTD) signals. These so called movement-related cortical potentials (MRCPs) ( Shibasaki et al, 1980 ) have been shown to hold discriminable information of upper limb movements ( Ofner et al, 2017 ), different grasps ( Agashe et al, 2015 ; Jochumsen et al, 2016 ), different reach-and-grasp actions ( Randazzo et al, 2015 ; Iturrate et al, 2018 ; Schwarz et al, 2018 , 2019 ) and can even be decoded online ( Ofner et al, 2019 ; Schwarz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…By showing that subject-dependent classifiers were able to uncover discriminable patterns between pure passive motions and exoskeleton-assisted motor imagery, this work started to tackle several open questions regarding continuous control exploiting only EEG signals. As an alternative, we have recently shown that other neural correlates could be used for the control of similar systems [34], [35].…”
Section: Discussionmentioning
confidence: 99%
“…Implementar una BCI multimodal que pueda decodificar la intención de movimiento antes que este se produzca es clave para brindar esa sensación de comando natural del dispositivo de asistencia del miembro superior. Muchos trabajos han sido publicados en la literatura científica alrededor de esta problemática [35,[57][58][59][60][61][62][63][64], sin embargo este tipo de BCI actualmente requieren de largos periodos de entrenamiento para lograr un nivel aceptable de naturalidad al comandar el dispositivo de asistencia del miembro superior, esto hace que en la mayoría de los casos pierdan el interés en el uso de este tipo de interfaces, este fenómeno inclusive ocurre en sujetos sanos.…”
Section: Mejora Del Desempeño De Detección De Patronesunclassified